Role of Blockchain in Enhancing Cybersecurity and Efficiency in International Trade - Talla, Rajasekhar Reddy (American Journal of Trade and Policy, 2023)
This research examines how blockchain technology improves international commerce cybersecurity and efficiency. We want to see how blockchain enhances transparency, reduces costs, and streamlines global trading networks by addressing security risks and inefficiencies. Secondary data-based literature reviews, case studies, and industry reports are used to assess blockchain’s trade potential. The research found that blockchain improves cybersecurity by decentralizing data storage, assuring immutability, and preventing fraud and data breaches. Automation via smart contracts, trade paperwork simplification, and supply chain visibility boost efficiency. However, scalability, interoperability, and regulatory issues persist. The report underlines that blockchain may lower costs by removing intermediaries and increasing direct peer-to-peer interactions. Standards, cross-border legislation, and incentives for blockchain implementation, especially for SMEs, have policy implications. It also emphasizes stakeholder engagement and capacity-building to overcome technical and financial hurdles. The research finds that blockchain may transform international commerce by making it safer, more efficient, and transparent, but it needs concerted governmental initiatives to overcome present constraints.